First-principles study of crystal and electronic structures and magnetic property for NaFeCr(WO4)2 compounds - N, Tsogbadrakh; L, Nyam-Ochir; Kh, Tsookhuu; S.C, Hong (Scientific transaction of the National University of Mongolia. Physics, 2022)
We have first studied the crystal and electronic structures, and magnetic property for sodium double tungstate NaFexCr 1-x(WO 4)2 (x =0, 0.50 and 1.0) compounds using the plane wave self-consistent method within the framework of density functional theory (DFT). We show that the ground state of sodium double tungstate compounds is the antiferromagnetic (AFM) state. We emphasize that the AFM coupling on the bc plane is generated by the 90 o superexchange mechanism. While the AFM coupling of the long-range magnetic interaction between the layers along the a - axis is generated by the Na mediated super - superexchange mechanism.